Bank Risk and Bank Size on the Efficiency of Islamic Banks (Study on Islamic Commercial Banks Registered with the Financial Services Authority 2018–2024) - Utami, Intan Sukma; Sundari, Siti (JURNAL MANAJEMEN MOTIVASI, 2026)
This study analyzes the impact of financing risk and bank size on the efficiency of Islamic Commercial Banks (BUS) in Indonesia from 2018 to 2024. Efficiency is measured using the Data Envelopment Analysis (DEA) method with an intermediation approach, while panel data regression is used for hypothesis testing. The Common Effect Model (CEM) is identified as the best fit. Results show that financing risk (NPF) negatively affects efficiency, while bank size (TASET) has a positive effect. These findings highlight the importance of effective risk management and asset scale optimization in improving the operational efficiency of Islamic banks.